Educating the Precariat: Intern Labour and a Renewed Approach to Media Literacy Education - Doug Tewksbury (tripleC: Communication, Capitalism & Critique)
As internships have become more common in the production of media content, the media literacy movement has been neglectful in addressing the role of labour in general and internship labour in particular as a necessary component in deconstructing media content. This paper argues that media literacy educators should teach citizens to understand not just the content and grammar of media production, but also the labour conditions that underlie the creation of this content, with internships being among the most exploitative development in recent years and representative of a larger issue of worker precarity. The paper concludes with a call for reforms to media literacy pedagogy to address workers’ rights and dignity in media and creative industries.